1969
DOI: 10.1111/j.1600-0765.1969.tb01950.x
|View full text |Cite
|
Sign up to set email alerts
|

The histology of the muco‐gingival junction

Abstract: Nineteen pieces of muco‐gingival tissue from man and monkey were examined by histological and histochemical methods. Neither a surface groove nor a change from keratinisation to non‐keratinisation were consistently seen in all specimens; the differing elastic tissue content of the gingiva and alveolar mucosa was therefore used to define the muco‐gingival junction. The surface groove, the keratinisation pattern, the distribution of hydrolytic enzymes and the glycogen content have been related to this junction. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
15
1
1

Year Published

1974
1974
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 6 publications
4
15
1
1
Order By: Relevance
“…In the past, AM connective tissue has been characterized by heavier deposition of elastin in the comparison of attached gingiva [12,13]. Indeed, the current study demonstrated that AM contained significant amounts of 2 elastin-derived crosslinks, IsoDES and DES (0.1-0.14 residues/1,000) (Table 1), whereas they were undetectable in AG.…”
Section: Discussioncontrasting
confidence: 44%
See 1 more Smart Citation
“…In the past, AM connective tissue has been characterized by heavier deposition of elastin in the comparison of attached gingiva [12,13]. Indeed, the current study demonstrated that AM contained significant amounts of 2 elastin-derived crosslinks, IsoDES and DES (0.1-0.14 residues/1,000) (Table 1), whereas they were undetectable in AG.…”
Section: Discussioncontrasting
confidence: 44%
“…In contrast to these studies for gingival collagen, almost no information is available about collagen in alveolar mucosa. This tissue has been characterized as a tissue with heavier deposition of elastin [12,13]. As a first step toward understanding the biochemical composition and nature of alveolar mucosa, we partially characterized the collagen of this tissue and compared it with that of the attached gingiva obtained from the same animals.…”
Section: Introductionmentioning
confidence: 99%
“…2 Histological and histochemical criteria for the definition of the alveolar mucosa include the increased amount of glycogen in the epithelium, [3][4][5] the change in the distribution of acid phosphatase and non-specific esterase, [5][6][7] and -most characteristically -the sudden, marked increase in elastic fiber content within the corium. 5,8 Although the need for a so-called "adequate" amount of KT for maintenance of periodontal health is questionable, [9][10][11][12][13] the MGJ often serves as a landmark for measurements in periodontal evaluations. Assessment of gingival dimensions, including the apico-coronal dimension and thickness of KT, is essential to decision-making in periodontal treatment planning, specifically to establish whether and what type of periodontal surgical procedure should be performed.…”
mentioning
confidence: 99%
“…Mukogingivalna linija može se proceniti i vizuelno posle bojenja mukogingivalnog kompleksa Lugolovim rastvorom (jodna proba). Alveolarna sluzokoža razlikuje se od keratinizovane gingive u sadržaju glikogena, kisele fosfataze i nespecifične esteraze i povećanoj količini elastičnih vlakana, što rezultira u pozitivnoj jodnoj reakciji [6][7][8][9] .…”
Section: Uvodunclassified
“…Mucogingival line can be assessed visually after staining the mucogingival complex with Lugol solution (iodine test). Alveolar mucosa differs from the gingival curettage in glycogen, acid phosphatase, and the non-specific esterase, and an increased amount of elastic fibers, resulting in a positive reaction on iodine [6][7][8][9] . The attached gingiva, which is keratinized, does not contain glycogen so that the surface layer provides a negative iodine reaction.…”
Section: Introductionmentioning
confidence: 99%